LEGAL GROUNDS FOR PRIVACY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article will review the genesis of the reasonable expectation of privacy REP requirement, both to establish the governing legal framework and to demonstrate how changing technology has altered our conception of the privacy in the past Ð°nd describes the limits and ability of government agents to search for and seize evidence without a warrant. It is difficult to consider these questions or to develop their significance in isolation from the specific doctrinal issues beneath which they lurk. With the reasonable expectation of privacy doctrine so limited, or even jettisoned altogether in favor of a dictionary definition of search, courts can properly turn their focus to what intrusions are reasonable. This Article concludes by examining four potential guideposts in this determination the right to privacy, principles of legality, proportionality and necessity.